ARTIFICIAL INTELLIGENCE AND FUTURE BUSINESS PROSPECTS': A GENERAL ANALYSIS - Anurag Hazarika; Samikshya Madhukullya; Anwesha Hazarika (Proceedings on Engineering Sciences)
In the business sector, artificial intelligence (AI) is quickly becoming a disruptive force that is changing industries and redefining competitive dynamics. In order to give a thorough analysis, this research uses secondary data sources to investigate the potential business applications of artificial intelligence. We determine important trends and possible effects of AI on different sectors by reviewing the literature that has already been written, industry reports, and market studies. The approach focuses on combining information from reliable sources to provide insights into how AI might improve operational effectiveness, spur innovation, and develop new business models. According to our research, artificial intelligence (AI) will keep up its disruptive streak in the business world, giving organizations the ability to make data-driven decisions, automate repetitive jobs, and improve consumer experiences. It is anticipated that the integration of AI technologies, such as robotic process automation, natural language processing, and machine learning, would result in considerable cost reductions and productivity increases. Furthermore, by enabling tailored marketing, predictive analytics, and astute product development, AI is ready to offer up new business opportunities. But there are drawbacks to AI adoption as well, such as moral dilemmas, workforce displacement, and the requirement for legal frameworks. Companies need to invest in upskilling their employees and cultivate a culture of continuous learning in order to meet these challenges.